Regulation and targeting of enzymes mediating Parkinson's disease pathogenesis: focus on Parkinson's disease Kinases, GTPases and ATPases - Veerle Baekelandt (Frontiers Research Topics, 2015)
Understanding the molecular pathogenesis of Parkinson's disease (PD) is a priority in biomedical research and a pre-requisite to improve early disease diagnosis and ultimately to developing disease-modifying strategies. In the past decade and a half, geneticists have identified several genes that are involved in the molecular pathogenesis of PD. They not only identified gene variants segregating with familial forms of PD but also genetic risk factors of sporadic PD via genome-wide association studies (GWAS). Understanding how PD genes and their gene products function holds the promise of unraveling key PD pathogenic processes. Therefore the precise cellular role of PD proteins is currently the subject of intense investigation. Interestingly, a number of PD proteins have enzymatic functions, including kinase, GTPase or ATPase functions. In the context of understanding disease pathogenesis or developing disease-modifying therapies, enzymes possess several useful features. Firstly, enzymes are often key elements of cellular signaling networks, acting as on-off switches to determine signaling intensity. For instance, kinases mediate phosphorylation events, which activate or inactivate their substrates, while GTPases modulate activity of their effector proteins via direct interaction in a GDP/GTP dependent manner. ATPases also control cellular processes through their involvement in cellular energy production and/or in transmembrane transport. Secondly, enzymes are attractive targets for therapeutics development. This is exemplified by the growing number of kinase inhibitors approved for clinical use, while compounds modulating GTPases or ATPases have also been proposed as potential therapeutics. Finally, as elements in cellular signaling networks, enzymes are not generally constitutively active but subject to further regulation through additional signaling components. Knowledge of how PD kinases, GTPases and ATPases are activated or inactivated can aid in understanding how PD signaling networks are deregulated in disease and point to new possibilities in targeting pathological signaling processes. The objective of this research topic is to provide an overview of current knowledge on the regulation of cellular signaling networks of PD kinases, GTPases and ATPases. Both upstream and downstream signaling events will be covered, with a focus on molecular events that can readily be monitored (relevance as disease biomarkers) and have a potential to be modulated (relevance as potential therapeutic target).